2008
DOI: 10.1097/01.hp.0000303105.91168.ea
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dose From Radiological Examination for Scoliosis in Children Among Two Pediatric Hospitals by Monte Carlo Simulation

Abstract: The radiation exposures of children undergoing full spine radiography were investigated in two pediatric hospitals in Greece. Entrance surface kerma (Ka,e) was assessed by thermoluminescence dosimetry and patient's effective dose (E) was estimated by Monte Carlo simulation. All required information regarding patient age and sex, the irradiation geometry, the x-ray spectra, and other exposure parameters (tube voltage and current) were registered as well. Values of Ka,e were measured to range from 0.22 mGy to 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Total radiation risk is best quantified by the use of the effective dose, which is a reliable measure of the stochastic risk for the induction of cancer. The mean effective dose observed with one postero-anterior wholespine exposition, which covers a large part of the body and may be responsible for high cumulative doses, ranges from 0.05 to 0.5 mSv [10,11]. Supplementary lateral views and follow-up studies (up to 20 during adolescence) increase the cumulative effect and may be responsible for a significant dose delivered to the thyroid, breast and genitals.…”
Section: Discussionmentioning
confidence: 97%
“…Total radiation risk is best quantified by the use of the effective dose, which is a reliable measure of the stochastic risk for the induction of cancer. The mean effective dose observed with one postero-anterior wholespine exposition, which covers a large part of the body and may be responsible for high cumulative doses, ranges from 0.05 to 0.5 mSv [10,11]. Supplementary lateral views and follow-up studies (up to 20 during adolescence) increase the cumulative effect and may be responsible for a significant dose delivered to the thyroid, breast and genitals.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have examined the radiation exposure during the assessment of scoliosis patients [6][7][8][9][10][11][12]; however, we could identify only one previous study examining the intraoperative radiation exposure in children with FDA device/drug status: Not applicable. Author disclosures: NM: Nothing to disclose.…”
Section: Introductionmentioning
confidence: 88%
“…The fact that these numbers were so drastically altered by adjusting the mechanics of the radiographic imaging led to the study’s recommendation to use PA films rather than AP films. Gialousis et al also found that the PA approach could reduce the increased risk of breast cancer in females treated for scoliosis [6]. …”
Section: The Epidemiology Of X-ray Exposure In Pediatric Patients Witmentioning
confidence: 99%